An Information System Model for Higher Certificate Management in Thai Supply Chain - Artaphon Chansamut (International Journal of Supply Chain Management, 2022)
The purpose of this research aim to develop an information system model for higher certificate management in Thai supply chain. The research was conducted with research and development methodusing questionnaires, and the model was assessed by experts. The research found there were five type of an information system model for higher certificate management in Thai supply chain namely Raw materials, Supplier, organization ( Manufacturer) , Finished product and Customers. The data analysed by using arithmetic mean and standard deviation . an information system model for higher certificate management in Thai supply chain using Back-Box technique. The results from experts have evaluated the model and commented that the model is high level of appropriateness.